2001
DOI: 10.1002/ana.66
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin (ACTH) acts directly on amygdala neurons to down‐regulate corticotropin‐releasing hormone gene expression

Abstract: The hormone corticotropin (ACTH) is employed as therapy for diverse neurological disorders, but the mechanisms for its efficacy remain unknown. ACTH promotes the release of adrenal steroids (glucocorticoids), and most ACTH effects on the central nervous system (CNS) have been attributed to activation of glucocorticoid receptors. However, in several human disorders, ACTH has therapeutic actions that differ qualitatively or quantitatively from those of steroids. This study tested the hypothesis that ACTH directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 51 publications
0
78
0
Order By: Relevance
“…However, MTII acting directly on adrenal MC2R likely increases corticosterone release in comparison to the selective MC4R agonist PF446687, and the heightened stress activation may counteract effects on adult prosociality in MTII-treated male voles. Additionally, MC4R stimulation in the central amygdala leads to reductions in CRF mRNA (Brunson et al, 2001). It is therefore possible that the modulation of stress axis by MC4R underlies the observed changes in adult sociality.…”
Section: Discussionmentioning
confidence: 99%
“…However, MTII acting directly on adrenal MC2R likely increases corticosterone release in comparison to the selective MC4R agonist PF446687, and the heightened stress activation may counteract effects on adult prosociality in MTII-treated male voles. Additionally, MC4R stimulation in the central amygdala leads to reductions in CRF mRNA (Brunson et al, 2001). It is therefore possible that the modulation of stress axis by MC4R underlies the observed changes in adult sociality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested immunosuppressive effect of ACTH and corticosteroids, together with anti-inflammatory properties, as well as direct inhibitory impact on CNS excitability and possible inhibition of endogenous proconvulsant factor synthesis (Baram & Hatalski 1998, Riikonen 2000, Brunson, Khan, Eghbal-Ahmadi & Baram 2001, Joels & Baram 2009, Vezzani, French, Bartfai & Baram 2011), although ACTH has been reported to be more efficient (Snead 2001). In addition, therapy with immune-modulatory agents such as ACTH and corticosteroids or high-dose immunoglobulin has shown efficacy on spasms cessation in some patients with IS of infectious etiology, however it was suggested that steroid therapy should be avoided in patients with a history of CMV and herpes simplex in the past (Ariizumi, Shiihara, Hibio, Ryo, Baba, Ogawa et al 1983, Ariizumi, Baba, Hibio, Shiihara, Michihiro, Ogawa et al 1987, Riikonen 1993, Wise, Rutledge & Kuzniecky 1996, Hattori 2001).…”
Section: Are There Any Lead Candidates or Unexplored Targets For Fmentioning
confidence: 99%
“…In support of this, one study has shown that a single i.p. injection of a high dose of ACTH 4-10 (80 IU/Kg) – having a high affinity for melanocortin receptors - reduced CRF mRNA receptor expression in the central nucleus of the amygdala [25]. This effect was blocked by the melanocortocotropin MC4 receptor antagonist SHU919, indicating that activation of melanocortin receptors are responsible for the effect of ACTH in reducing CRF receptor expression in the amygdala [25].…”
Section: Discussionmentioning
confidence: 99%
“…injection of a high dose of ACTH 4-10 (80 IU/Kg) – having a high affinity for melanocortin receptors - reduced CRF mRNA receptor expression in the central nucleus of the amygdala [25]. This effect was blocked by the melanocortocotropin MC4 receptor antagonist SHU919, indicating that activation of melanocortin receptors are responsible for the effect of ACTH in reducing CRF receptor expression in the amygdala [25]. Furthermore, a recent study has shown that activation of MC4 receptors located post-synaptically in the hippocampus results in enhanced LTP due to a protein kinase A-dependent up-regulation in the surface expression of GluA1-containing AMPA receptors which are involved in the morphological maturation and number of dendritic spines [26].…”
Section: Discussionmentioning
confidence: 99%